Ranibizumab and aflibercept for the treatment of wet age-related macular degeneration. (September 2015) - Yazdi, Mohammad Hossein; Faramarzi, Mohammad Ali; Nikfar, Shekoufeh; Falavarjani, Khalil Ghasemi; Abdollahi, Mohammad
<x xml:space="preserve">Abstract</x> Introduction: Wet age-related macular degeneration (AMD) is a potentially blinding eye disease that causes vision loss among individuals > 50 years old. The main goal in the treatment of wet AMD is to inhibit the choroidal neovascularization (CNV). Currently, ranibizumab and aflibercept are two available anti-VEGF drug for the treatment of wet AMD. Here, we reviewed the clinical outcome of treatment with ranibizumab or aflibercept in patients with wet AMD from recent studies with a special focus on eyes with unusual presentations or treatment resistant and compared these agents with other available wet AMD therapies. Areas covered: For this review, a literature search from 2011 to present was performed using the following terms (or combination of terms): anti-vascular endothelial growth factors, anti-VEGF, age-related macular degeneration, AMD, aflibercept, and ranibizumab. The studies were limited to studies used ranibizumab, and especially those switched from ranibizumab to aflibercept. Also the clinical trial website (www.clinicaltrials.gov) was searched for recently completed trials of aflibercept or ranibizumab for wet AMD treatment. Expert opinion: Ranibizumab and aflibercept are effective for the treatment of wet AMD including those with retinal angiomatous proliferation (RAP) and CNV unresponsive to other anti-VEGF agents. Although high-dose ranibizumab has the potential to treat unresponsive CNV, switching to another anti-VEGF agent may be a preferable option in these eyes.